Root distribution of 'Valência' orange under traveler gun irrigation - Testezlaf, Roberto; Coletti, Christiane; Matsura, Edson Eiji (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to evaluate root distribution of 36 years old 'Valência' oranges with Citrus limonia Osbeck rootstock, under traveler gun irrigation, in Typic Hapludox. Soil samples were taken from five trees in two orthogonal radii, one in the direction of the crop rows and the other in between rows, at 60 cm depth. The root system distribution was determined by dry weight of the roots with diameters equal or less than 1.5 mm. The 0–40 cm soil layer showed the larger percentage of root, with reduction of root concentration from the end of the tree canopy to between rows.